COMPARATIVE OUTCOMES OF EXTRACORPOREAL KNOT-TYING SUTURES VERSUS METALLIC ENDO-CLIPS IN LAPAROSCOPIC APPENDICEAL STUMP CLOSURE FOR ACUTE APPENDICITIS - NIAZ , MI; ANWAR , M; SABIR , M; ANWAR , S; AKHTAR , N; RASHEED , U (Biological and Clinical Sciences Research Journal, 2024)
Acute appendicitis is one of the most common indications for emergency surgery and it has a lifetime incidence of 7 %. Characteristic presentation of acute appendicitis includes periumbilical pain, nausea, fever, and right lower quadrant pain and tenderness. Appendectomy can be done open and by Laparoscopy. Objective: To compare Appendiceal base leakage, mean duration of surgery, and mean post-operative hospital stay in extracorporeal knot tying suture versus metallic endo - clips in laparoscopic Appendiceal stump closure in patients with acute appendicitis Methods: In this study, 70 patients were randomly divided into two groups using the lottery method. Group A consisted of 35 patients in whom metallic endo-clips were used, while Group B included 35 patients with extracorporeal knotting techniques. The mesoappendix in both groups was divided using a LigaSure device, and the appendix was retrieved from the abdomen through a 10mm laparoscopic port. Results: Out of the 70 patients in the study, 44 (62.9%) were male, and 26 (37.1%) were female. Male to female ratio was 1.7:1. The mean age of the participants was 30.24 ± 7.73 years, with the youngest patient being 21 years old and the oldest being 50 years old. The mean age for male patients was 29.66 ± 8.38 years, while the mean age for female patients was 31.23 ± 6.52 years, with no statistically significant difference between the two (p=0.415). Most patients, 57 (81.4%), were aged up to 30 years. Regarding residency, 22 (31.4%) patients were from rural areas, and 48 (68.6%) were from urban areas. Socioeconomically, 21 (30.0%) patients were from a lower-income background, while 49 (70.0%) were from a middle-income background. The mean body mass index (BMI) of the patients was 25.31 ± 1.92 kg/m², with 11 (15.7%) patients classified as obese. Regarding surgical outcomes, the mean duration of surgery was significantly shorter in Group A, at 28.89 ± 2.42 minutes, compared to Group B, which had a mean duration of 34.23 ± 1.68 minutes (p<0.001). However, the mean duration of hospital stay was similar between the two groups, with Group A having a mean stay of 31.54 ± 6.54 hours and Group B having a mean stay of 31.37 ± 5.49 hours (p=0.906), indicating no significant difference. Complications were observed in only 4 (4.3%) patients, with 2.9% in Group A and 5.7% in Group B (p=0.998). Conclusion: Our study demonstrates that using metallic endo-clips for laparoscopic appendiceal stump closure in patients with acute appendicitis is more efficient than extracorporeal knot tying. The use of endo-clips significantly reduces the duration of the surgical procedure, thereby saving valuable time for the surgical team. Additionally, this technique is associated with a shorter postoperative hospital stay and a lower incidence of complications such as appendiceal base leakage and surgical site infections.